Output intensity of LED light curing units in dental offices of Piura, Peru - Crista Gadith Palacios Rivas; Dora Denisse Cruz Flores; Carmen Teresa Ibáñez Sevilla; MIGUEL ANGEL RUIZ-BARRUETO (Revista Cubana de Estomatología, 2022)
Introduction: Light curing lamps that use light-emitting diodes (LED) are used in dentistry for the polymeric conversion of dental restorative materials. It has been reported that inadequate light intensity in the lamp would not ensure the appropriate polymerization of restorative materials.